A cascaded enzyme-loaded Fe–hemoporfin framework for synergistic sonodynamic-starvation therapy of tumors. Issue 11 (16th March 2021) - Wen, Mei; Shen, Jiayue; Wang, Zhaojie; Guo, Honghua; Geng, Peng; Yu, Nuo; Li, Maoquan; Zhang, Haijun; Zhu, Meifang; Chen, Zhigang
Abstract : The FeHF–GOx/CAT system exhibited synergistic SDT–starvation therapy and achieved high therapeutic efficiency for cancer cells. Abstract : Enzyme-loaded nanosystems with multimodal therapeutic functions have received increasing attention in the treatment of malignant tumors. Herein, we designed and prepared cascaded dual-enzyme-augmented Fe–hemoporfin framework nanosonosensitizers for synergistic sonodynamic-starvation therapy of tumors. Amorphous Fe–hemoporfin frameworks (FeHF) with an average size of ∼85 nm were synthesized by assembling the clinical drug hemoporfin with Fe 3+ ions. Then, FeHF was used to load dual enzymes (glucose oxidase (GOx) and catalase (CAT)) and modified by PEGylated folic acid-conjugated lipids. The dual-enzyme loaded FeHF (FeHF–GOx/CAT) exhibited higher efficiency not only for glucose depletion but also for ultrasound (US)-triggered 1 O2 generation than that of pure FeHF, resulting from the cascaded catalytic reaction from the dual-enzyme system. As observed by magnetic resonance imaging, the intravenously injected FeHF–GOx/CAT was accumulated within tumors. The FeHF–GOx/CAT + US exhibited the highest inhibition effect compared to the FeHF–CAT + US (only SDT) or FeHF–GOx/CAT (only starvation therapy), due to the synergistic effects of SDT and starvation therapy. Therefore, the cascaded dual-enzyme loading strategy can increase the SDT efficiency of FeHF, which may guide further works in the development of efficient nanosonosensitizers.